The Relationship Between Knowledge and Attitudes with Tuberculosis Prevention Measures in Adolescents - Rahmawati, Shinta Alifiana; Abdullah, Akbar Amin; Suhariyati, Suhariyati; Rohmah, Amrina Nur Rohmah; Irawan, Dwi Dianita; Rahmawati, Elia I (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Approximately one-quarter of the global population is estimated to be infected with tuberculosis (TB). TB is an infectious disease caused by Mycobacterium tuberculosis and remains the second leading cause of death from infectious diseases worldwide after COVID-19. Transmission of TB occurs through airborne droplets released from respiratory secretions. Indonesia ranks second globally in terms of the number of TB cases. This study aimed to determine the relationship between knowledge and attitudes with measures to prevent tuberculosis in adolescents. Methods: This study employed an analytical design using a survey method with a correlational approach. Bivariate analysis was conducted using Kendall’s tau, while multivariate analysis was performed using linear regression. The study population consisted of 293 adolescents, with a sample of 75 respondents selected using a quota sampling technique. Results: The results of the analysis of knowledge and attitudes using kendall tau obtained a p-value = 0.001 and p-value = 0.000 and linear regression obtained a p-value = 0.000. Conclusion: There is a significant relationship between knowledge and attitudes with tuberculosis prevention practices among adolescents. Suggestions to further improve TB prevention measures, especially regarding covering the mouth when coughing, balanced nutritional intake, and healthy living behavior.